PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE ROTATING TRIO EXCHANGE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 33 PADANG - Gunawan, Ade; Rahmi, M.Si, Dra.; Pertiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACTComprehension of mathematical concept of students in class VIII of SMPN 33 that still low. It causes less of interaction from the students so that they have not share knowledge with their friends. One way that is used to overcome this problems is Rotating Trio Exchange. This research was aimed at revealing whether the use of Rotating Trio Exchange strategies could give a better effect on the students comprehension of mathematical concept than the conventional learning in class VIII of SMPN 33 Padang. This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in students comprehension of mathematical concept. Based on the result of data analysis, it was revealed that the sample was distributed normally and homogeny variant. Hypothesis test results obtained  tcount = 3.3218 and ttable = 1.6710,  indicating that the hypothesis was accepted. So, it was concluded that the application of Rotating Trio Exchange strategies could improve the students comprehension of  mathematical concept  better than the conventional learning.